The Islamicization of architecture and environmental design education - Mohd. Yaman, Maheran; Ibrahim, Mansor (Common Ground Publishing Pty Ltd, 2007)
Environment is a ramified source to testify the truth of the Islamic ilm (education). Iqra (the first word in Quran revealation meaning to read) through environment is the way of instilling the future human capital in practice in order to gain not just worldly material gain but also spiritually development. The philosophy of ‘garden of knowledge and virtue’ adopted by IIUM could be testified for such purpose. This is achieved by the implementing of triple IIICE that becomes the niche of IIUM’s education approach which is ‘tauhidic (oneness)’ orientated. Knowledge shall be propagated in the spirit of tawhid leading towards the recognition of Allah as the absolute Creator and Master of mankind. This represents the apex in the hierarchy of knowledge. Knowledge is a trust (amanah) from Allah and its development shall be in conformity with the purpose behind Allah’s creation of the universe. Knowledge should be utilised by man, as the servant (‘abid) of Allah and vicegerent (khalifah) on earth, in accordance with the will of Allah. The quest for knowledge is regarded as an act of worship (‘ibadah). KAED aims at becoming a leading international centre of educational excellence which seeks to restore the dynamic and progressive role of the Muslim Ummah (society) in all environmental related programmes. The ‘niche areas’ can be the methods applied in a particular discipline or programme, i.e. Islamicization of curriculum. Islamicization refers to the process of integration of the revealed knowledge and “acquired knowledge” such as Islamic ethics and professional knowledge. The paper reviews KAED’s approach in designing and implementing its programmes. The feedbacks from the students and professional are also surveyed for further improvement.